CURRENT STATUS AND NEEDS OF CONTINUING PROFESSIONAL TRAINING OF NURSES IN PEDIATRIC DEPARTMENTS, NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY, NINH BINH PROVINCE (Vietnam Journal of Community Medicine, 2022)
Objective: This study was conducted to determine the current status and need for continuingprofessional training of nurses at the pediatric departments, the Hospital of Obstetrics andGynecology, Ninh Binh Province.Methods: This is a cross-sectional study conducted on 121 subjects who are nurses from thepediatric departments at the Hospital of Obstetrics and Pediatrics, Ninh Binh province, from7/2021 to 6/2022. The study subjects were convenient sampling. We use a self-designed setof questions.Results: In terms of training status, in 2019-2020, training courses at the Hospital havetrained 100% of pediatric nurses at the hospital. The number of nurses sent for trainingat central level institutions accounts for a low proportion (17.36%). Compared to 2019,the number of training sessions at the Hospital will be nearly four times higher in 2020.However, the number of training sessions at central-level facilities is three times lower.Regarding training needs, out of 6 techniques in pediatrics, there are two techniques with alow proficiency level that need to be prioritized for training. In addition, there are two othertechniques with medium proficiency that can be supervised training. All 17 techniques inemergency have intermediate practice proficiency. Therefore, all of these techniques havetraining needs at the level of supervised training.Conclusion: The results of our study show that it is advisable to focus on deploying trainingmodels with techniques with low proficiency. In addition, continuing training classes at theHospital need to strengthen the form of practical training.
Keywords: Continuing professional training, nursing, pediatric departments.